Environment and livelihoods in tropical coastal zone managing agriculture- fishery -aquaculture conflicts. (Oxon, U.K. CABI House Office, 2006)
Comprehensive assessment of water management in agricultural series, 2
Keywords: Coastal zone management; Fisheries; Agriculture; Aquaculture